2020
DOI: 10.1101/gad.340133.120
|View full text |Cite
|
Sign up to set email alerts
|

MYCN drives chemoresistance in small cell lung cancer while USP7 inhibition can restore chemosensitivity

Abstract: Small cell lung cancer (SCLC) is an aggressive neuroendocrine cancer characterized by initial chemosensitivity followed by emergence of chemoresistant disease. To study roles for MYCN amplification in SCLC progression and chemoresistance, we developed a genetically engineered mouse model of MYCN-overexpressing SCLC. In treatment-naïve mice, MYCN overexpression promoted cell cycle progression, suppressed infiltration of cytotoxic T cells, and accelerated SCLC. MYCN overexpression also suppressed response to cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 73 publications
2
33
1
Order By: Relevance
“…In a matched pair of CDX, the percentage of MYC + cells increased with tumor progression, concordant with increased expression of Notch signaling and EMT markers ( Simpson et al 2020 ). These findings are consistent in GEMMs, where high expression of MYC or MYCN and low expression of NE markers correspond with poor response to chemotherapy ( Mollaoglu et al 2017 ; Grunblatt et al 2020 ). In human cell lines, MYC protein levels also increased (while MYCL decreased) following selection for chemoresistance ( Wagner et al 2018 ; Chalishazar et al 2019 ; Huang et al 2021 ).…”
Section: A Revised and Evolving Classification Scheme Based On Lineag...supporting
confidence: 78%
“…In a matched pair of CDX, the percentage of MYC + cells increased with tumor progression, concordant with increased expression of Notch signaling and EMT markers ( Simpson et al 2020 ). These findings are consistent in GEMMs, where high expression of MYC or MYCN and low expression of NE markers correspond with poor response to chemotherapy ( Mollaoglu et al 2017 ; Grunblatt et al 2020 ). In human cell lines, MYC protein levels also increased (while MYCL decreased) following selection for chemoresistance ( Wagner et al 2018 ; Chalishazar et al 2019 ; Huang et al 2021 ).…”
Section: A Revised and Evolving Classification Scheme Based On Lineag...supporting
confidence: 78%
“…33,35 The abnormal expression of MYCN was found in neurogenic tumors, including neuroblastoma, neuroendocrine prostate cancer and small cell lung cancer. [36][37][38][39][40]…”
Section: Discussionmentioning
confidence: 99%
“…Using a PDX model, Grunblatt et al identified the deubiquitinase USP7 as a MYCN-associated synthetic vulnerability in small cell lung cancer (SCLC) by a genome-scale CRISPR-Cas9 screening. Pharmacological inhibition of USP7 re-sensitized chemo-resistant MYCN-overexpressing PDX models to chemotherapy in vivo ( 218 ). Similarly, dihydroorotate dehydrogenase was also identified as a therapeutic target in SCLC cells ( 219 ).…”
Section: The Combined Application Of the Crispr-cas9 Screening And Pa...mentioning
confidence: 99%